Performative Transactions: Artistic Collaboration of Humans and AI Agents in Decentralized Creative Networks - Łukawski, Adam (Boca Raton, FL, US CRC Press, Taylor&Francis, 2024)
This chapter introduces two new concepts: ‘Decentralized Creative Networks’ and ‘Performative Transactions’. Decentralized Creative Networks are envisioned as blockchain-based post-human social networks, in which artists and AI agents develop and transact composable artistic processes, transparently building upon each other’s interoperable contributions. These processes are shared in Decentralized Creative Networks like social media posts. Artists can use them to shape their artistic work, by making it dependent on the execution of processes created by other artists and AI agents (for instance to compose music, to execute live performances of an artistic work, or to generate non-fungible tokens). Performative Transaction is a kind of transaction specific to these networks. It is executed by a smart contract, the code of which specifies both the artistic process and the terms of referencing it by other processes. To ensure interoperability, artistic processes in the system are composed as recursive patterns of transformations in a framework inspired by the Transformational Theory of David Lewin and Machine Learning’s feature engineering. When interlinked Performative Transactions are executed, smart contracts carry out all referenced musical transformations contributing to the musical result. They also automatically distribute any financial receivables to the creators of all referenced artistic processes. Furthermore, the integration of Artificial Intelligence within Decentralized Creative Networks is discussed, suggesting a collaborative framework where human and AI agents interact, actively shaping the artistic network. These interactions are further elucidated on the examples of music composition, performance, analysis, and sound synthesis, demonstrating the versatility of Performative Transactions for musical use cases. While recognizing the potential of Decentralized Creative Networks, the chapter acknowledges current challenges for their development. Overcoming these challenges could significantly impact how art is created, shared, and experienced in the digital era.
FRIS
Editorial review
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music; Music